Emergency Combination of Four Drugs for Bloodstream Infection Caused by Carbapenem-Resistant Enterobacteriaceae in Severe Agranulocytosis Patients with Hematologic Malignancies after Hematopoietic Stem Cell Transplantation. (4th August 2020) - Li, Xiaofan; Hong, Yaqun; Chen, Xianling; Chen, Ping; Li, Nainong
Abstract : Bloodstream infection (BSI) caused by multidrug-resistant (MDR) bacteria or extensively drug-resistant (XDR) bacteria is a global threat. However, an effective treatment regimen is still controversial and inadequate due to the rapid deterioration caused by the bacteria. In immunocompromised and neutropenic patients, MDR-BSI is an emergency, which causes treatment-related mortality. In this study, four agranulocytosis patients with hematologic malignancies after HSCT receiving treatment for carbapenem-resistant Enterobacteriaceae - (CRE-) BSI were included. Conventional treatment using two to three combined antibiotics was administered in the first and second patients. Combination treatment using four drugs, polymyxin B, high-dose tigecycline, fosfomycin, and double-dose carbapenem, was administered in the third and fourth patients. None of the patients receiving conventional treatment survived. Both patients receiving combination treatment using four drugs survived. Therefore, four-drug combination therapy may be needed in CRE-BSI patients who experienced severe agranulocytosis after HSCT. The efficacy of the four-drug combination treatment for CRE-BSI patients as well as the adverse effects need to be further studied.